2021
DOI: 10.21203/rs.3.rs-409667/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis on Catastrophic Cost Incurred by Tuberculosis Patients

Abstract: Background: One of the World Health Organization End Tuberculosis (TB) Strategy is to reduce the proportion of TB affected families facing catastrophic costs (CC) to 0% by 2020. CC is defined if total cost related to TB management exceeded 20% of annual pre-TB household income. This study aimed to estimate the pooled proportion (PP) of TB affected households who suffered from CC. Method: A search of the online database through September 2020 was performed. Of 5114 articles, 29 articles were included in meta-an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…As a result, MDR-TB patients often suffer high out-of-pocket (OOP) expenditures and, loss of incomes because of extended treatment course (9). A recent systematic review reported that 80% patients with MDR-TB faced catastrophic cost at 20% household's annual income (10). In low-and -middle-income countries, the per patient cost was relatively lower, but still enough to incur high proportion of catastrophic cost (6).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, MDR-TB patients often suffer high out-of-pocket (OOP) expenditures and, loss of incomes because of extended treatment course (9). A recent systematic review reported that 80% patients with MDR-TB faced catastrophic cost at 20% household's annual income (10). In low-and -middle-income countries, the per patient cost was relatively lower, but still enough to incur high proportion of catastrophic cost (6).…”
Section: Introductionmentioning
confidence: 99%